A Study of working population in Uttar Dinajpur District, West Bengal - Roy, Arpita; Verma, Narender (National Geographical Journal of India, 2022)
Work is dened as participation in any economically productive activity with or without compensation, wages or prot. Such participation may be physical and/or mental. Work involves not only actual work but also includes effective supervision and direction of work. Work Participation Rate shows the proportion of working population to total population in an area and is computed as the percentage of total workers (main and marginal) to the total population. The social and economic development of any region is greatly inuenced by the number of economically active persons, their quality and the regularity of the work. In this respect, work participation rates are very useful to understand the level of economic development of a region as it differs from the stages of economic development. This paper attempts to study the Work Participation Rate among different categories of workers in Uttar Dinajpur district. It is one of the country's 250 most backward districts and more than two-thirds of its active workforce still draws livelihood directly from agriculture and related occupations. The present study is census data based. From the result, it can be observed that the work participation rate is a little high in Raiganj Sub-division than in the Islampur Sub-division. Although the work participation rates of men are much higher than those for women in both rural and urban areas women's work participation in the district has risen at a faster rate than that of men.